Durable Flame-Retardant Cotton Fabric Modified by a Novel Reactive P-N Intumescent Flame Retardant - Denghui Wu; Xinhang Li; Peihua Zhao (Advances in Polymer Technology)
A novel reactive P-N intumescent flame retardant tetroxo (3-triethylphosphine-5-chlorine-1-triazine) neopentane (TTCTN) was prepared, and its structure was determined by Fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR). The flame retardance and physiological comfort properties of TTCTN-treated cotton fabrics (TTCTN-CF) was researched. The CF treated with 20 wt% TTCTN (TTCTN(20)-CF) showed the limiting oxygen index (LOI) was up to 28.6%, and the flame retardancy reached the class B1 of national standard of flame retardant fabrics, and its peak heat release rate and total heat release were reduced by 55.7% and 37.4% comparing with untreated CF, respectively. The FTIR proved the TTCTN was grafted on the CF matrix. Thermogravimetric (TG) showed TTCTN could reduce the decomposition speed of the cotton fabric and formed the stable char residue at high temperature to protect the remaining CF from complete dehydration. After 50 washing cycles, the LOI of TTCTN(20)-CF was 26.2%, still reaching class B1 of national standard of flame retardant fabrics. Scanning electron microscope showed the TTCTN was still bounded to the matrix of CF after 50 washing cycles which further proved TTCTN(20)-CF had excellent durable flame retardancy.